2013
DOI: 10.1136/emermed-2013-203238
|View full text |Cite
|
Sign up to set email alerts
|

Acute pesticide poisoning outcomes: a nationwide study in Taiwan

Abstract: In APP patients, treatment by a high-volume physician can reduce LOS and treatment cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Fifth, because we identified intoxication events based on ICD9 codes and the antidotes administered, there may have been some misclassification. However, previous studies based on similar databases showed reliable results [2,12,[47][48][49][50][51]. Our current research thus provides an overview of intoxication events in Taiwan between 2006 and 2013.…”
Section: Strengths and Limitationssupporting
confidence: 51%
“…Fifth, because we identified intoxication events based on ICD9 codes and the antidotes administered, there may have been some misclassification. However, previous studies based on similar databases showed reliable results [2,12,[47][48][49][50][51]. Our current research thus provides an overview of intoxication events in Taiwan between 2006 and 2013.…”
Section: Strengths and Limitationssupporting
confidence: 51%
“…11,12 However, in a South African and a Taiwanese study, there were more female cases of acute poisoning with pesticides where most were related to organophosphate poisoning. 13,14 This study found that 51.7% of organophosphate poisonings were intentional, whereas 21.7% were accidental and 26.6% had unknown circumstances. Similarly, a study from India showed 64.6% of cases of intentional poisoning, 34.4% of accidental poisoning, and 1% of unknown circumstances.…”
Section: Discussionmentioning
confidence: 87%
“…11,12 However, in a South African and a Taiwanese study, there were more female cases of acute poisoning with pesticides where most were related to organophosphate poisoning. 13,14…”
Section: Discussionmentioning
confidence: 99%
“…Third, because we identi ed intoxication events based on ICD9 codes and the antidotes administered, there may have been some misclassi cation. However, previous studies based on similar databases showed reliable results (22,(37)(38)(39)(40)(41)(42). Our current research thus provides an overview of intoxication events in Taiwan between 2006 and 2013.…”
Section: Strengths and Limitationsmentioning
confidence: 88%